Yargı etiği ilkeleri - Çakar, Rümeysa (My University, 2020)
Yargı etiği, yargılama faaliyetlerine ilişkin etik ölçütleri ortaya koyan bir meslek etiğidir. Yargı etiği; yargının eşitlik, bağımsızlık, tarafsızlık, dürüstlük, doğruluk, tutarlılık, ehliyet ve liyakat sahibi olma, insan onurunu, mahremiyeti ve yargıya güveni koruma şeklindeki değerlerini yargı etiği ilkeleri ile ortaya koymaktadır. Yargı etiği ilkeleri ise yargı etiğine ilişkin bu temel değerlerin gerekliliği ifade eden önermeler şeklinde formüle edilmeleri ile oluşturulmuştur. Yargı etiği ilkeleri, hâkimlerin yargı etiği değerlerini benimseyerek kendilerini etik birer özneye dönüştürmelerine ve etik bir yargı düzeninin oluşturulmasına hizmet etmektedir. Bu çalışmada yargı etiği ilkelerinin bilgisi, ilkeleri oluşturan değerler ile ilkelerin uygulanmasına yönelik olan davranış kuralları açıklanarak ortaya konulmuştur.

Jurisdiction ethics is an ethics of profession which sets forth the ethical standards relating to jurisdiction. Jurisdiction ethics presents judgment values, which are equality, detachedness, objectivity, honesty, accuracy, coherency, to be competent and merit holder, to protect human dignity, privacy, and trust in the jurisdiction, with the principles of jurisdiction ethics. As for the principles of jurisdiction ethics, they are constituted by being formulated as premises stating the necessity of these fundamental values regarding the jurisdiction ethics. The principles of jurisdiction ethics serve for creating an ethical judicial system and for Judges and Public Prosecutors to turn themselves into ethical subjects by adopting values of jurisdiction ethics. In this study, knowledge of jurisdiction ethics principles, values forming these principles, and rules of conduct devoted to the execution of the principles have been manifested by being clarified.
Keywords: Bangalor Yargı Etik İlkeleri; Bangalore Principles of Judicial Conduct; Etik; Judicial ethics; Kamu hukuku; Meslek Etiği; Practical Ethics; Pratik Etik; Principles of Judicial Ethics; Professional Ethics; Public law; Turkish Declaration of Judicial Ethics; Türk Yargı Etik Bildirgesi Ethic; Yargı etiği; Yargı Etiği İlkeleri